DIVERSITE MORPHOLOGIQUE DES VARIETES LOCALES DE MAÏS (ZEA MAYS L.) COLLECTEES AU CENTRE ET CENTRE-OUEST DE LA COTE D’IVOIRE - Annicet N’DA, Hugues; Akanvou, Louise; Konan Kouakou, Charles; Irié Bi Zoro, Arsène (European Scientific Journal, ESJ, 2014)
Morphological characterization is a first approach to the study ofgenetic diversity. Nine hundred twenty maize accessions collected in thecenter and center-west of Côte d’Ivoire, were evaluated morphologically in ablock randomized design. Thirteen morphological descriptors were used inthis study. The descriptive analysis revealed a significant diversity amongaccessions, marked by a significant gap between the minimum andmaximum values. The principal components analysis summarized theinformation contained in the thirteen variables into 3 components that render78.28% of the total variance. The hierarchical clustering allowed us todistinguish two main groups based on early and plant height. Each group wassubdivided into 4 subgroups. Descriptive discriminant analysis showed thateight variables (days to 50% pollen shedding, days to 50% silking, plantheight, ear height, leaf number, number of kernels per row, length of ears),contribute most to discriminate the different subgroups. Different subgroupscan serve parents in the creation of improved varieties.